Identidade, prática docente e características ocupacionais dos professores dos cursos de graduação em enfermagem do estado de Goiás - Paulino, Valquiria Coelho Pina (2016)
The overall objective of the study was to analyze the teaching identity, practice and training of teachers of undergraduate courses in public and private nursing in the state of Goiás. Methodology: Field research, descriptive cross-sectional. The sample consisted of 213 teachers which corresponds to 74.2% of professionals in undergraduate courses in Nursing, 60 linked to public and private courses to 153. For collection, we used a questionnaire addressing the teacher identity in personal, professional and administrative dimensions. Data were tabulated in Microsoft ® Excel 2010 program and the statistical analysis by SPSS program for Windows, version 16.0. Results: In the personal dimension the predominant age group was 30-51 years, and the oldest are in public institutions. In the professional dimension, the prevailing academic courses in Pubic was the doctorate and private in the Masters. As for specific training for teaching 85% of teachers were public courses and 73.8% in private. In the administrative dimension, public courses, the working time average in higher education was 11.13 years, 81.7% statutory, 81.7% worked exclusively at the university, with average weekly working hours of 38.53 hours, and 11.3 hours for education, 7.97 hours for planning and 19.3 hours for research and extension activities, 55% earned more than 8 times the minimum wage. Among the participants, 86.7% have published at least one article in a scientific journal and 70% in conference proceedings in the last three years. The greatest difficulty pointed to the teaching exercise was the workload and demand for production and qualification (31.6%). In private courses, the working time average in higher education is 8.95 years, 79.1% were hourly, with weekly working hours of 42.46 hours, and the average in education 23.7 hours and 6.76 hours of planning, having no specific time for research. As for workplaces, 39.2% worked in two or more institutions and 28.1% earned over 8 minimum wages, 22.9% have published at least one work in conference proceedings and 37.3% in the journal three years. The greatest difficulty pointed to the teaching exercise was the lack of interest and intellectual training of students (37.2%). Conclusions: There are differences in the teaching identity, practice and training of teachers of public and private institutions in this respect confirming the first hypothesis established for the study. The second hypothesis was refuted because, teachers in both types of courses studied, most have specific training for teaching and there is a search movement of teachers for qualifying.